2010
DOI: 10.1143/jjap.49.04dc06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hundreds of Time Constant Ratios and Amplitudes of Random Telegraph Signal with Very Large Scale Array Test Pattern

Abstract: Random telegraph signal (RTS) noise shows discrete and stochastic switching in two or more states at a drain current or threshold voltage. The capture and emission of carriers in individual traps near a silicon–gate insulator film interface induce RTS noise phenomena. RTS noise has become a crucial problem in analog devices and other devices. To suppress RTS noise, it is necessary to determine the energy level of traps. Time constant ratio has a strong relationship with the energy level of traps in gate insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The time constants can be extracted with µs accuracy using the specific MOSFET measurement mode. The time constant ratio <τe>/<τc> is also an important parameter in RTN because the energy level of a trap that causes RTN is related to the constant ratio as follows [12,[41][42][43].…”
Section: Extraction Of Amplitude and Time Constant Of Rtnmentioning
confidence: 99%
See 1 more Smart Citation
“…The time constants can be extracted with µs accuracy using the specific MOSFET measurement mode. The time constant ratio <τe>/<τc> is also an important parameter in RTN because the energy level of a trap that causes RTN is related to the constant ratio as follows [12,[41][42][43].…”
Section: Extraction Of Amplitude and Time Constant Of Rtnmentioning
confidence: 99%
“…where ET and EF represent the energy of the trap and Fermi energy of the channel, respectively; k, T, and g represent Boltzmann constant, temperature, and degeneracy factor, re- The time constant ratio <τ e >/<τ c > is also an important parameter in RTN because the energy level of a trap that causes RTN is related to the constant ratio as follows [12,[41][42][43].…”
Section: Extraction Of Amplitude and Time Constant Of Rtnmentioning
confidence: 99%
“…The pixels with high RNs (blinking or twinkling pixels [7][8][9]) will create fixed-pattern temporal noises flickering from frame to frame. It is known that most of the pixels on the long distribution tails show the behavior of the random telegraph signals (RTS) [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Such noises are called the RTS noises, or the random telegraph noises (RTN).…”
Section: Introductionmentioning
confidence: 99%
“…A general study of the RTS phenomena in semiconductor devices can be found in a recent book [24], covering a wide range of experimental and theoretical topics. For CIS, the most reported RTN originate from the source followers (SF) of the active pixels [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Although other sources, such as DC-RTS, have been reported [25,26], a comprehensive discrimination and comparison of the various sources of RTN in a CIS cannot be found in the literature yet.…”
Section: Introductionmentioning
confidence: 99%
“…To fully understand the RTN, it is necessary to characterize the statistical distributions, emission-capture time constants, activation energies, noise power spectra densities, physical locations, and the relations to detailed fabrication processes. In spite of being studied in the past several decades [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], many RTN-related issues still remain as active research topics due to the nature of its complexity.…”
Section: Introductionmentioning
confidence: 99%